2008
DOI: 10.1111/j.1530-0277.2008.00628.x
|View full text |Cite
|
Sign up to set email alerts
|

Fingerprint Profile of Alcohol‐Associated Heart Failure in Human Hearts

Abstract: We report for the first time a genomic "fingerprint" profile of de-regulated genes associated with human alcohol-induced heart failure. We conclude that the pathogenesis of alcohol-induced heart failure in humans is likely related to changes in architectural (e.g. cytoskeletal), matrix, and/or structural proteins. The reversibility of the disease upon cessation of alcohol consumption makes this a likely pathogenetic mechanism. Nevertheless, there is a point at which extracellular as well as cellular changes re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 49 publications
(54 reference statements)
0
9
0
Order By: Relevance
“…In that regard, microarray studies performed on cardiac tissue from alcoholic human males showed a down‐regulation in key extracellular matrix genes like titin, collagen type III, and calponin. These data allude to alcohol‐induced etiology of heart failure (Haddad et al., ).…”
Section: Pathogenesis Of Alcohol‐induced Cardiomyopathymentioning
confidence: 97%
“…In that regard, microarray studies performed on cardiac tissue from alcoholic human males showed a down‐regulation in key extracellular matrix genes like titin, collagen type III, and calponin. These data allude to alcohol‐induced etiology of heart failure (Haddad et al., ).…”
Section: Pathogenesis Of Alcohol‐induced Cardiomyopathymentioning
confidence: 97%
“…Adversely, chronic HA consumption has various detrimental effects leading to alcoholic cardiomyopathy (Krenz and Korthuis, 2012). Our laboratory and others have linked the Akt pathway as a mediator of alcohol-induced translational diminishment of anti-apoptotic signals (Chen et al, 2000; Haddad et al, 2008). Akt pathway has been heavily studied with its association with induced oxidative stress (Ma and Wang, 2012), which may be linked to cardiomyopathy.…”
mentioning
confidence: 99%
“…The clinical relevance of this fi nding is unclear, however. Although excessive alcohol consumption is recognized as a cause of HF (Haddad et al, 2008), light to moderate alcohol consumption (up to one drink daily for women and one or two drinks daily for men) seems benefi cial in preventing CAD and CAD-related HF in healthy persons (Djousse and Gaziano, 2007;Klatsky et al, 2005;O'Keefe et al, 2007). However, because alcohol consumption increases blood pressure and thereby hypertension risk in a dose-dependent fashion (Beilin and Puddey, 2006), it may be speculated that benefi ts of moderate alcohol consumption on CAD might be counterbalanced in HF patients who are more vulnerable to blood pressure effects (Klatsky, 2004;Klatsky and Gunderson, 2006;Walsh et al, 2002).…”
Section: Discussionmentioning
confidence: 99%